2018
DOI: 10.31031/mapp.2018.01.000518
|View full text |Cite
|
Sign up to set email alerts
|

"In Vitro Studies on Alpha Amylase Inhibitory Activity of Some Indigenous Plants"

Abstract: Diabetes mellitus is a chronic metabolic disorder characterized by high blood glucose level caused due to deficiency of insulin secretion or insulin action. It includes a group of metabolic diseases characterized by hyperglycemia, in which blood sugar levels are elevated either because the pancreas do not produce enough insulin or cells do not respond to the produced insulin. Thus, a therapeutic approach to treat diabetes is to decrease postprandial hyperglycemia in patients with type II diabetes. It can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 18 publications
0
60
0
3
Order By: Relevance
“…The inhibition of α-amylase activity was carried out by dinitrosalicylic acid (DNS) method [52]. Briefly, 1 mL of the extract (50, 100, or 200 µg/mL) or acarbose (100 µg/mL) was pre-incubated with 1 mL of α-amylase (A4582, diluted for 10,000 in 20 mM sodium phosphate buffer, pH 6.9) for 30 min before adding 1 mL (1% w/v) of starch solution.…”
Section: Alpha-amylase Inhibitory Assaymentioning
confidence: 99%
“…The inhibition of α-amylase activity was carried out by dinitrosalicylic acid (DNS) method [52]. Briefly, 1 mL of the extract (50, 100, or 200 µg/mL) or acarbose (100 µg/mL) was pre-incubated with 1 mL of α-amylase (A4582, diluted for 10,000 in 20 mM sodium phosphate buffer, pH 6.9) for 30 min before adding 1 mL (1% w/v) of starch solution.…”
Section: Alpha-amylase Inhibitory Assaymentioning
confidence: 99%
“…The amount of maltose liberated during the reaction in units was used to represent the enzyme inhibition activity. A modified Dinitrosalicylic acid (DNS) procedure was used for the determination of maltose equivalent [16]. The experiment was initiated by pre-incubation of 1ml of the methanolic extract of V. grandiflorum for 30 min with α-amylase 1U/mL and then 1 ml (1% w/v) of starch solution was added.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…They commonly used strong allopathic drugs which possess a number of harmful side effects. Bhutkar and Bhise (2012) used the aqueous extracts from leaves, stems, seeds and roots of selected plants such as Tamarindus indica, Catharanthus roseus and Caesalpinia bonducella which are used in the ayurvedic traditional system of medicine to treat diabetes, for their inhibitory effect on α-amylase 16 . The results revealed that the aqueous extracts of leaves of T.indica, extracts from the stems and roots of C. roseus and C. bonducella exhibited significant (more than 70%) reduction in α-amylase activity.…”
Section: Figure5 α-Amylase Inhibitory Activity Of Costus Igneus Gymmentioning
confidence: 99%